Why rankings of biomedical image analysis competitions should be interpreted with care - Maier-Hein, Lena; Eisenmann, Matthias; Reinke, Annika; Onogur, Sinan; Stankovic, Marko; Scholz, Patrick; Arbel, Tal; Bogunovic, Hrvoje; Bradley, Andrew P; Carass, Aaron; Feldmann, Carolin; Frangi, Alejandro F; et al. (Nature communications, 2018)
International challenges have become the standard for validation of biomedical image analysis methods. Given their scientific impact, it is surprising that a critical analysis of common practices related to the organization of challenges has not yet been performed. In this paper, we present a comprehensive analysis of biomedical image analysis challenges conducted up to now. We demonstrate the importance of challenges and show that the lack of quality control has critical consequences. First, reproducibility and interpretation of the results is often hampered as only a fraction of relevant information is typically provided. Second, the rank of an algorithm is generally not robust to a number of variables such as the test data used for validation, the ranking scheme applied and the observers that make the reference annotations. To overcome these problems, we recommend best practice guidelines and define open research questions to be addressed in the future.
Keywords: Technology Assessment, Biomedical; biomedicínský výzkum; průzkumy a dotazníky; Image Processing, Computer-Assisted; Reproducibility of Results; Humans; Biomedical Research; biomedicínské technologie; hodnocení biomedicínských technologií; Diagnostic Imaging; reprodukovatelnost výsledků; Surveys and Questionnaires; Biomedical Technology; lidé; počítačové zpracování obrazu; diagnostické zobrazování